Silencing ACE1 Gene with dsRNA of Different Lengths Impairs Larval Development in Leptinotarsa decemlineata - Brenda Julian-Chávez; Tania S. Siqueiros-Cendón; Jorge Ariel Torres-Castillo; Sugey Ramona Sinagawa-García; María Jazmín Abraham-Juárez; Carmen Daniela González-Barriga; Quintín Rascón-Cruz; Luis Ignacio Siañez-Estrada; Sigifredo Arévalo-Gallegos; Edward Alexander Espinoza-Sánchez (Insects)
In the search for effective strategies to control the Colorado Potato Beetle, RNA interference technology has emerged as a promising method due to its capacity to suppress genes selectively. Factors such as the target gene and double-stranded RNA (dsRNA) length are critical for optimizing gene silencing efficiency. In this study, we designed and synthesized in vitro dsRNAs of varying lengths targeting the ACE1 gene, which encodes the AChE1 isoform of acetylcholinesterase in the beetle. All tested dsRNA lengths (222 bp, 543 bp, 670 bp, and 870 bp) promoted transcript reduction. The 670 bp dsRNA was the most effective, reducing transcript levels by approximately 40% by day seven, followed by the 543 bp dsRNA. No significant differences were observed between the 222 bp and 870 bp dsRNAs. Furthermore, all of the dsRNA lengths resulted in reduced weight gain and increased mortality in larvae, with the 670 bp dsRNA showing the highest mortality rate, leaving only 63% larval survival, a trend that persisted through day nine. These findings emphasize that dsRNA length is a key factor in the silencing response, underscoring the importance of selecting the optimal length while considering the gene’s target, stability, and delivery methods. This study contributes to establishing design criteria for dsRNA, aiding in the development of more effective and sustainable pest management strategies.